THE COMPLEX DYNAMICS OF AIR POLLUTION AND ITS VARIED IMPACTS - MAKHMADIYOROVA MOTABAR TOSHKANOVNA, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Air pollution remains a pressing global issue with significant implications for human health, environmental sustainability, and socioeconomic stability. This thesis aims to delve into the nuanced aspects of air pollution, examining its diverse sources, regional disparities, specific health effects, environmental consequences, and the effectiveness of mitigation strategies.